Sejarah Pemikiran Kebangsaan Jakob Oetama Pada Surat Kabar Kompas 1970-2001 - Nusaibah, Annida Allim; Abrar, Abrar; Martini, Sri (Universitas Hamzanwadi, 2021)
Nationality is needed by every Indonesian as one of the efforts to continue maintaining the unity and integrity of the nation. One of the national press figures who seriously think about the issue of nationality is Jakob Oetama. One of the ways Jakob Oetama channeled national ideology was through the press media named the Kompas. The purpose of this study was to find out how Jakob Oetama ideology about nationality in Kompas newspaper. The period is from 1970 to 2001. The research method uses historical research methods consisting of four stages; heuristics, verification, interpretation and historiography. The results showed that Jakob Oetama's national ideology in the first Kompas daily newspaper was Bhinneka Tunggal Ika and national ideology, national integration and disintegration, religious issues, knowing the homeland, and the principle of transcendental humanism.Pemahaman kebangsaan sangat diperlukan oleh setiap rakyat Indonesia sebagai salah satu upaya untuk terus mempertahankan persatuan dan kesatuan bangsa. Salah satu tokoh pers nasional yang serius memikirkan persoalan tentang kebangsaan adalah Jakob Oetama. Cara Jakob Oetama menyalurkan pemikiran kebangsaan salah satunya yaitu lewat media pers yang diberi nama surat kabar Kompas. Tujuan penelitian ini adalah untuk mengetahui bagaimana pemikiran Jakob Oetama tentang kebangsaan pada surat kabar Kompas periode tahun 1970 sampai dengan tahun 2001. Penelitian ini menggunakan metode penelitian sejarah yang terdiri dari empat tahap yaitu, heuristik, verifikasi, interpretasi dan historiografi. Hasil penelitian menunjukan bahwa pemikiran kebangsaan Jakob Oetama pada surat kabar harian Kompas adalah Bhinneka Tunggal Ika dan ideologi kebangsaan, integrasi dan disintegrasi nasional, persoalan agama, mengenal tanah air, dan prinsip humanisme transendental.